2019
DOI: 10.1038/s41467-019-08586-3
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of BCL9/9l suppresses Wnt driven tumourigenesis in models that recapitulate human cancer

Abstract: Different thresholds of Wnt signalling are thought to drive stem cell maintenance, regeneration, differentiation and cancer. However, the principle that oncogenic Wnt signalling could be specifically targeted remains controversial. Here we examine the requirement of BCL9/9l, constituents of the Wnt-enhanceosome, for intestinal transformation following loss of the tumour suppressor APC. Although required for Lgr5+ intestinal stem cells and regeneration, Bcl9/9l deletion has no impact upon normal intestinal home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 60 publications
7
83
0
Order By: Relevance
“…This was surprising, since BCL9/9L proteins were thought to act as mere "bridge" proteins that tethered PYGO to the b-catenin transcriptional complex ( Figure 1A) (Fiedler et al, 2015;Mosimann et al, 2009). Both BCL9 and PYGO proteins have been implicated in colorectal carcinogenesis (Gay et al, 2019;Jiang et al, 2020;Mieszczanek et al, 2019;Talla and Brembeck, 2016). We tested if the consequence of the deletion of Bcl9/9l and Pygo1/2 genes was also different in the context of carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was surprising, since BCL9/9L proteins were thought to act as mere "bridge" proteins that tethered PYGO to the b-catenin transcriptional complex ( Figure 1A) (Fiedler et al, 2015;Mosimann et al, 2009). Both BCL9 and PYGO proteins have been implicated in colorectal carcinogenesis (Gay et al, 2019;Jiang et al, 2020;Mieszczanek et al, 2019;Talla and Brembeck, 2016). We tested if the consequence of the deletion of Bcl9/9l and Pygo1/2 genes was also different in the context of carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously however, BCL9 and PYGO always seem to act as a "duet" (Kennedy et al, 2010). Importantly, BCL9/9L and PYGO proteins were found to significantly contribute to the malignant traits typical of Wnt-induced CRCs (Deka et al, 2010;Gay et al, 2019;Jiang et al, 2020;Mani et al, 2009;Mieszczanek et al, 2019;Moor et al, 2015;Talla and Brembeck, 2016). These observations provided impetus to consider the BCL9/PYGO axis as relevant "targetable" unit in CRC (Lyou et al, 2017;Mieszczanek et al, 2019;Talla and Brembeck, 2016;Zimmerli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperproliferative IESCs expressing only Ctnnb1 D164A have an increased ability to form organoids Recent work indicated that intestinal organoids could not be established from BCL9/9Ldeficient crypts isolated 4d pi 14 . However, we hypothesized that expansion of the proliferative IESC compartment in D164A crypts observed 2d pi would translate into increased organoid formation rate.…”
Section: Intestinal Crypts Lacking the Output Via Of N-terminal Recrumentioning
confidence: 99%
“…Conversely, B-cell lymphoma 9 (BCL9) or the paralog BCL9-like (BCL9L) specifically bind an N-terminal moiety of β-catenin, and act as tissue-specific transcriptional effectors [7][8][9][10][11] . While dispensable for normal intestinal homeostasis, BCL9/9L are required for intestinal regeneration upon insults [12][13][14][15] , suggesting that they might be necessary for the reconstitution of the stem cell pool. Moreover, compelling evidence has been provided that BCL9/9L plays a crucial role in maintaining tumor stemness in several murine models of colorectal cancer [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation